STRATEGI KEPEMIMPINAN ADAPTIF DALAM MENGEMBANGKAN LINGKUNGAN BELAJAR YANG INKLUSIF DAN BERBASIS TEKNOLOGI - Iif Pratiwi; Endah Widyati; Saukani Saukani (STKIP Pesisir Selatan, 2026)
This study aims to analyze adaptive leadership strategies in developing an inclusive, technology-based learning environment. The method employed is a literature review (library research) by examining relevant and up-to-date journal articles, academic books, conference proceedings, and policy reports on adaptive leadership, inclusive education, and the integration of learning technologies. The data were analyzed using content analysis/thematic analysis through the stages of source selection, key information extraction, grouping of findings, and thematic synthesis. The review identifies six main themes: (1) mapping technical and adaptive challenges as a basis for intervention, (2) strengthening a collaborative culture across roles, (3) continuous professional development for meaningful technology integration, (4) establishing accessibility standards and implementing Universal Design for Learning (UDL), (5) leveraging learning data for equitable interventions, and (6) strengthening leaders’ digital literacy and change governance. The findings emphasize that adaptive leadership functions as an integrative mechanism between the agendas of digitalization and inclusion, ensuring that technology serves to enhance access, participation, and the quality of learning. This study recommends establishing “inclusive digital” collaboration structures, standardizing minimum accessibility requirements based on UDL, and implementing data-driven evaluation to support equitable learning outcomes.